Mechanical stratigraphy influences deformation band pattern in arkosic sandstones, Rio do Peixe Basin, Brazil. (February 2022) - Oliveira, L.S.B.; Nogueira, F.C.C.; Vasconcelos, D.L.; Balsamo, F.; Bezerra, F.H.R.; Pérez, Y.A.R.
Abstract: This study shows how mechanical stratigraphy influences deformation bands' structural attributes in faulted, heterolithic arkosic sandstones in the Rio do Peixe Basin, northeastern Brazil. We combined the analyses of sedimentary units with rock properties (porosity, permeability, Young's modulus, Poisson's ratio, and uniaxial compressive strength) and structural data to characterize the mechanical units and related deformation band pattern. Our results show that deformation bands have differences in frequency, geometry, thickness, and dip in different mechanical units. In addition, sedimentary parameters as grain size, layer thickness, stratification, cementation, and mineral composition impact the vertical propagation of deformation bands. In each layer, deformation bands frequency increases approaching a normal fault, and the dip of the deformation bands varies when passing through layers. In the studied mechanical units, deformation band density increases with increasing host rock porosity and decreasing Young's modulus. Finally, we document that the development of deformation bands increases the overall cohesion of the fault zone, particularly in units with coarser grain sizes. Our results have implications for mechanical stratigraphy in faulted siliciclastic reservoirs. Graphical abstract: Image 1 Highlights: Mechanical stratigraphy controls frequency and thickness of deformation bands. Grain size and layer thickness influence the deformation bands geometry patterns. Deformation bands increase the rock cohesion and decrease the porosity/permeability. The highest deformation bands frequency implies the lowest Young modulus.